Thermophilic Behavior of Heat-Dissociative Coacervate Droplets - Kim, Youngsun; Zheng, Yuebing (American Chemical Society, 2024)
In exploring the genesis of life, liquid-liquid phase-separated coacervate droplets have been proposed as primitive protocells. Within the hydrothermal hypothesis, these droplets would emerge from molecule-rich hot fluids and thus be subjected to temperature gradients. Investigating their thermophoretic behavior can provide insights into protocell footprints in thermal landscapes, advancing our understanding of life's origins. Here, we report the thermophilic behavior of heat-dissociative droplets, contrary to the intuition that heat-associative condensates would prefer hotter areas. This aspect implies the preferential presence of heat-dissociative primordial condensates near hydrothermal environments, facilitating molecular incorporation and biochemical syntheses. Additionally, our investigations reveal similarities between thermophoretic and electrophoretic motions, dictated by molecular redistribution within droplets due to their fluid nature, which necessitates revising current electrophoresis frameworks for surface charge characterization. Our study elucidates how coacervate droplets navigate thermal and electric fields, reveals their thermal-landscape-dependent molecular characteristics, and bridges foundational theories of early life: the hydrothermal and condensate-as-protocell hypotheses.